The Legal Status of Testaments That Eliminate the Inheritance Rights for the Longest-Living Marital Spouse - Indradewi, Astrid Athina; Achmad, Andyna Susiawati; Sugianto, Fajar (Magister Hukum Universitas Semarang, 2024)
The purpose of this study is to examine the legal standing of testaments that forgo a spouse's right to inherit in the event of their death. This study is necessary because, while everyone has the right to draft a testament according to their desires, this does not absolve the contents of the testament from being based on applicable laws and regulations. This study was carried out utilizing a doctrinal and statutory method in a normative juridical manner. The study concludes that a testator's intentions are free to be included in a will; nonetheless, the Indonesian Civil Code governs the legitimacy of Legitieme Portie. Thus, if a testament is written by a spouse whose marriage has entered into a marital agreement to separate assets, and its contents eliminate the longest-living spouse's inheritance rights, then that will not violate the rights of the longest-living spouse because it is based on Article 914 of the Indonesian Civil Code that the husband or wife does not have Legitime Portie. In the meantime, a testament written by a spouse whose marriage did not result in a marital agreement that separates assets only applies to the portion of the maker's assets; in other words, the longest-living spouse still receives a share as part of the joint assets in marriage.